GEOGRAPHIC INFORMATION SYSTEMS FOR THE DISTRIBUTION OF COMMUNITY SERVICE ACTIVITIES IN KUANTAN SINGINGI DISTRICT - Nofri Wandi Al Hafiz; M. Hasim Siregar (INFOKUM, 2021)
Villages where community service has been carried out so far the data will be stored in the LPPMDI archive file in the form of a work report, which annually will be given to LPMP for making lecturer performance reports, but LPPM itself does not yet have historical data on Community Service in the form of maps, so that villages that have been carried out activities or that have never been visited, cannot be presented in a visual form that can be accessed by many people, only limited to report data, besides that the problems that exist in each village in Kuantan Singingi Regency will be different, so a system is needed to describe and select potential and appropriate locations to serve as locations for community service and display the results of this service, villages where community service has been carried out have been mapped and seen the results of the community program the team appointed to implement it in the form of ideas the implementation team, the types of activities carried out, the targets to be achieved by the team in the service program, the results produced after the service, and activity documentation, all of this is entered into a system that can be seen in the form of maps, with the aim of being accessible to general users such as the public. or related institutions.